2009
DOI: 10.1103/physrevc.80.014601
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of break-up processes on the fusion ofO16induced reactions

Abstract: An experiment was carried out to explore heavy ion incomplete fusion reaction dynamics, within the framework of the break-up fusion model, at energies near and above the Coulomb barrier. Excitation functions for several radionuclides produced via xn, pxn, and αxn channels were measured in the 16 O + 181 Ta system at energies of ≈76-100 MeV. The experimental excitation functions were compared with those calculated using the theoretical model code PACE4. It was observed that excitation functions of xn/pxn channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Therefore, it can be safely inferred that the Q α is a rather more suitable parameter than binding energy to explain ICF data. In order to strengthen the above systematics, the values of F ICF for 12 C, 13 C, 16 O+ 159 Tb [44,53,73] and 12 C, 13 C, 16 O+ 181 Ta [46,49] systems have been compared in Figs. 8(a) and 8(b) as a functions of Q α at the same value of of v rel .…”
Section: Projectile Structure Dependence Of Icfmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it can be safely inferred that the Q α is a rather more suitable parameter than binding energy to explain ICF data. In order to strengthen the above systematics, the values of F ICF for 12 C, 13 C, 16 O+ 159 Tb [44,53,73] and 12 C, 13 C, 16 O+ 181 Ta [46,49] systems have been compared in Figs. 8(a) and 8(b) as a functions of Q α at the same value of of v rel .…”
Section: Projectile Structure Dependence Of Icfmentioning
confidence: 99%
“…Thus, a comparison of experimental EFs with the statistical model code PACE4 may indicate the extent to which the formation of identified ERs may be explained by the equilibrated CN decay. Any deviation in the experimental EFs with respect to the PACE4 predictions may be attributed to ICF, which is not included in this code [44][45][46][47][48]. channels.…”
Section: Analysis Of Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In this hypothesis they asummed a sharp cut-off approximation, according to which the probability of CF is asummed to be unity for = crit and expected to be zero for > crit . However, in recent time several studies have observed the occurrence of ICF processes in the vicinity of Coulomb barrier [5][6][7][8]. Yadav et al [5] has observed the existence of ICF reactions at < crit .…”
Section: Introductionmentioning
confidence: 99%